2022
DOI: 10.3389/fphar.2022.824015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Intra-Articular Injection of Triptolide-loaded Solid Lipid Nanoparticle for Treatment of Antigen-Induced Arthritis in Rabbits

Abstract: Objective: To evaluate the efficacy of ultrasound-guided intra-articular injection of triptolide-loaded solid lipid nanoparticle (TP-SLN) for treatment of antigen-induced arthritis (AIA) in rabbits. Material and Methods: Knee joints of 33 New Zealand rabbits with AIA were injected intra-articularly with triptolide (TP: n = 7), TP-SLN (n = 7), betamethasone (BS: n = 7) and dimethyl sulfoxide (DMSO: n = 6). The remaining six rabbits were untreated as the control group. The injection therapy in intervention group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…On the other hand, Compritol was chosen based on its hydrophobicity as it is composed of long-chain fatty acids [ 42 ]. Moreover, Compritol had been used in many studies for the fabrication of lipid nanocarriers for intraarticular drug injection for the treatment of arthritis [ 43 , 44 , 45 , 46 ]. In addition, cholesterol was included in the preparation to enhance the stabilization of the outer phospholipid layer besides being capable to augment loading and entrapment of hydrophobic drugs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Compritol was chosen based on its hydrophobicity as it is composed of long-chain fatty acids [ 42 ]. Moreover, Compritol had been used in many studies for the fabrication of lipid nanocarriers for intraarticular drug injection for the treatment of arthritis [ 43 , 44 , 45 , 46 ]. In addition, cholesterol was included in the preparation to enhance the stabilization of the outer phospholipid layer besides being capable to augment loading and entrapment of hydrophobic drugs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nano-particles have drawn a lot of interest in the field of medical research, especially when it comes to the development of drug-delivery systems for the treatment of various diseases [48]. The way RA is treated may drastically change if nanoparticles are used [49]. Recent studies have indicated that the delivery of medication to the desired area utilizing nano-carriers such as nano dendrimer and nano polymer has shown promising results in the treatment of conditions like RA [49].…”
Section: Nano-particles As Carriers For Ros Regulation Therapiesmentioning
confidence: 99%
“…The way RA is treated may drastically change if nanoparticles are used [49]. Recent studies have indicated that the delivery of medication to the desired area utilizing nano-carriers such as nano dendrimer and nano polymer has shown promising results in the treatment of conditions like RA [49]. Drug delivery methods using micro-and nanoparticles provide targeted administration of therapeutic medicines to the RA-affected area [49].…”
Section: Nano-particles As Carriers For Ros Regulation Therapiesmentioning
confidence: 99%
See 2 more Smart Citations